CREATING THE QUESTIONNAIRE TO DETERMINE THE EFFECT OF STRESS FACTORS ON INTERPERSONAL COMMUNICATION AND ADAPTATION OF SENIOR PRESCHOOLERS WITH SPECIAL NEEDS - Черних, Лариса Анатоліївна (Visnyk of V.N. Karazin Kharkiv National University. Series Psychology, 2019)
The article analyzes the concept of stress, stressful factors in senior preschool children with special needs. The types of stressful factors and signs of stress condition of the senior preschool children with special needs are determined. The indicators of social and psychological adaptability to stress of senior preschool children with special needs are determined. The questionnaire was developed to determine the inflence of stress factors on interpersonal communication between parents and a child with special needs, a child with peers, and checked its reliability and validity. All questions were related to stressful factors, interpersonal communication of the child with their parents or peers, and reflcted the context of various spheres of life ofsocial reality. The scales of the questionnaire were verifid using the method of parallel factor analysis, which determined the optimal number of factors. The high reliability indexes of the questionnaire scales according to the α-Kronbach criterion were obtained, which substantiates the expediency of using the created author’s questionnaire. Three types of validity were selected and substantiated: competitive, obvious, meaningful. The level of inflence of stressful factors was determined by the correlation of responses on scales of «interpersonal communication between parents and the child», «interpersonal сommunication of a child with peers» with a scale «the impact of social stressful factors», which was calculated using the correlation analysis Kendall. The discriminativeness of the questionnaire was calculated.